Thrilling tales from the tree house eaudiobook - Brallier, Max (Last Kids on Earth, 2021)
The first ever graphic novel in the New York Times bestselling The Last Kids on Earth series—now adapted for audio! A Netflix Original series Includes SIX brand new Last Kids short stories by Max Brallier! The kids and their monster buddies are hanging out in the tree house, when Jack launches into an epic, totally-heroic, super rad story of one of his many post-apocalyptic adventures. Of course, after he's finished, everyone's eager to one-up his tale with a story of their own. Soon, Quint, Dirk, June and Skaelka, and even Globlet regale the group with sometimes outrageous, often hilarious details of their action-packed escapades during the monster-zombie apocalypse. Their stories are capped off by a special double-length feature which will finally reveal the mysterious whereabouts of two villainous villains to prep listeners for the 7th book in the series coming Fall 2021!